The History of the Central Maghreb through Islamic Coinage from 85 AH / 704 CE to 1246 AH / 1830 CE. - moumouch, mohamed (Journal of Social Sciences and Humanities, 2016)
Since its incorporation under the banner of the Islamic Caliphate, the Islamic Maghreb witnessed significant political dynamics that led to the emergence of several Islamic states. This followed its period of affiliation with both the Umayyad Caliphate and the Abbasid Caliphate, a phase known as the “Age of Governors,” which lasted for nearly a century. Subsequently, independent polities emerged, often linked in their origins to doctrinal movements that arose in the eastern Islamic world and later spread westward. Among these was the Rustamid Dynasty, which established its capital in Tahert. The Sufri State of Sijilmasa was also founded in the city of Sijilmasa (140 AH / 757 CE) in the Tafilalt region of the far Maghreb. Additionally, the Idrisid Dynasty was established in the city of Fez.